Applications of basalt fibre in Portland cement systems - Levchuck, Natalia; Shlyahova, Ekatierina (Studia Ecologiae et Bioethicae, 2018)
While studying the research sources, the authors of the article investigated a number of issues concerning the physicochemical processes taking place in the Portland cement system with the addition of basalt fibre. A series of experiments was conducted to study the properties of basalt fibre treated with colloidal aluminium hydroxide, the technology of injection fibre into the concrete mixture was proposed and an analysis of the results of the experiment was presented.